Zigbee wireless sensor network localization evaluation schemewith weighted centroid method - Lonesy Thammavong; Khamphong Khongsomboon; Thanadol Tiengthong; Sathaporn Promwong (My University, 2018)
Using wireless communication system, appropriate and correct indoor localization with Zigbee sensor network and could provide interesting services and applications. In this study the Zigbee transmission model with positioning method by using the relative-span exponentially weighted centroid method for the indoor localization. The experimental results and analyze results are evaluated a distance error. The ZigBee transmission model in measurement consists of 121 positions with distance between positions to positions is 0.3 meter. The experimental setup at every position operated at frequency band from 2.3 GHz to 2.5 GHz. The accuracy of estimated position is considered in the term of distance error with the cumulative distribution function (CDF) of distance error is shown. The result presents optimal value for REWL is 0.2 and mean of distance error is 0.65 m.
Keywords: Centroid; Position (finance); Distance measurement; Indoor and Outdoor Localization Technologies